Fates of identified pioneer cells in the developing antennal nervous system of the grasshopper Schistocerca gregaria. Issue 1 (January 2016) - Ehrhardt, Erica; Graf, Philip; Kleele, Tatjana; Liu, Yu; Boyan, George
Abstract: In the early embryonic grasshopper, two pairs of sibling cells near the apex of the antenna pioneer its dorsal and ventral nerve tracts to the brain. En route, the growth cones of these pioneers contact a so-called base pioneer associated with each tract and which acts as a guidepost cell. Both apical and basal pioneers express stereotypic molecular labels allowing them to be uniquely identified. Although their developmental origins are largely understood, the fates of the respective pioneers remain unclear. We therefore employed the established cell death markers acridine orange and TUNEL to determine whether the apical and basal pioneers undergo apoptosis during embryogenesis. Our data reveal that the apical pioneers maintain a consistent molecular profile from their birth up to mid-embryogenesis, at which point the initial antennal nerve tracts to the brain have been established. Shortly after this the apical pioneers undergo apoptosis. Death occurs at a developmental stage similar to that reported elsewhere for pioneers in a leg – an homologous appendage. Base pioneers, by contrast, progressively change their molecular profile and can no longer be unequivocally identified after mid-embryogenesis. At no stage up to then do they exhibit death labels. If they persist, the base pioneers must be assumed to adopt a new role in the developing antennal nervous system. Highlights: The embryonic nervous system of the grasshopper antenna comprises two nerve tracts. Each tract is founded by a set of identified apical and basal pioneers. The fate of these pioneers was investigated using a range of molecular markers. We found that the apical pioneers undergo apoptosis after mid-embryogenesis. Base pioneers are not labeled by cell death markers, and may persist in the antenna.